2020
DOI: 10.3389/fpsyt.2019.00946
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatizing Attitudes Towards Mental Disorders Among Non-Mental Health Professionals in Six General Hospitals in Hunan Province

Abstract: Background: There have been few studies on the stigma associated with mental disorders among non-mental health professionals in general hospitals in China. This study seeks to explore mental health-related stigma and the desire for social distance among non-mental health professionals in general hospitals in Hunan Province in China. Methods: The study was carried out with 1123 non-mental health professionals in six general hospitals in Hunan Province by using a questionnaire with a case vignette describing eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
4
27
0
3
Order By: Relevance
“…On the other hand, it is possible that healthcare workers could benefit from professional mental health interventions more than they recognize or report, and that under-recognition is related to occupational culture, or to fear of stigma or being perceived as weak ( Alden et al., 2020 ). While a variety of countries were represented, four of every five participants were Chinese, and Chinese occupational culture may be a salient mediator of healthcare workers’ expressed preferences ( Wu et al., 2019 ), although this must be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is possible that healthcare workers could benefit from professional mental health interventions more than they recognize or report, and that under-recognition is related to occupational culture, or to fear of stigma or being perceived as weak ( Alden et al., 2020 ). While a variety of countries were represented, four of every five participants were Chinese, and Chinese occupational culture may be a salient mediator of healthcare workers’ expressed preferences ( Wu et al., 2019 ), although this must be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study of 1,123 non-mental health professionals in six general hospitals in Hunan Province showed that more than 70% of them believed that people with depression are dangerous (Wu et al, 2017(Wu et al, , 2019. Furthermore, a review indicated that this stigma is even widespread among mental health professionals (Schulze, 2007).…”
Section: Stigmamentioning
confidence: 99%
“…The pandemic has triggered a social, economic and health crisis that has had a major impact on our mental health, with several studies focusing on assessing its consequences. In general, most research points to the emergence of symptoms of anxiety, depression, sleep problems and post-traumatic stress disorder (PTSD) in a significant percentage of the population ( González et al, 2020 ; Mazza et al, 2020 ; Tanoue et al, 2020 ; Voitsidis et al, 2020 ; Wu et al, 2020 ), as well as in various specific groups, such as students ( Liu et al, 2020 ; Wang et al, 2020a , Wang et al, 2020b ) or health professionals ( Liu et al, 2020 ; Pappa et al, 2020 ; Romero et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%